2008
DOI: 10.1016/j.gene.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of a tandem-repeat galectin from the freshwater snail Biomphalaria glabrata, intermediate host of the human blood fluke Schistosoma mansoni

Abstract: In the present study, a tandem-repeat type galectin was characterized from an embryonic cell line (Bge) and circulating hemocytes of the snail Biomphalaria glabrata, intermediate host of the human blood fluke Schistosoma mansoni. The predicted B. glabrata galectin (BgGal) protein of 32 kDa possessed 2 carbohydrate recognition domains, each displaying 6 of 8 conserved amino acids involved in galactoside-binding activity. A recombinant BgGal (rBgGal) demonstrated hemagglutinating activity against rabbit erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 59 publications
4
69
0
Order By: Relevance
“…Haemocytes of Biomphalaria quickly recognise parasites and produce ROS to kill the invading pathogens. This is an important component of Biomphalaria cellular defences; it determines the susceptibility or resistance to schistosome infection and production of cercariae (bendeR et al 2007, yoSHino et al 2008, ittiPRaSeRt et al 2010, Moné et al 2011. Interference with the snail immune system through improving the antioxidant system may help the snails to overcome the infection-associated stress and finally lead to retarding parasite development.…”
Section: Discussionmentioning
confidence: 99%
“…Haemocytes of Biomphalaria quickly recognise parasites and produce ROS to kill the invading pathogens. This is an important component of Biomphalaria cellular defences; it determines the susceptibility or resistance to schistosome infection and production of cercariae (bendeR et al 2007, yoSHino et al 2008, ittiPRaSeRt et al 2010, Moné et al 2011. Interference with the snail immune system through improving the antioxidant system may help the snails to overcome the infection-associated stress and finally lead to retarding parasite development.…”
Section: Discussionmentioning
confidence: 99%
“…(59). Although similarities in the glycosylation of both the schistosome and snail are known (60,61), the actual ligands of the snail galectin remain unknown.…”
Section: N-glycosylation Of Oyster Hemocytes and Plasma-usingmentioning
confidence: 99%
“…Although similarities in the glycosylation of both the schistosome and snail are known (60,61), the actual ligands of the snail galectin remain unknown. As a parallel with the oyster-Perkinsus interaction (54), it was proposed that the snail galectin may participate in host-Schistosoma interactions, yet to be determined (59). However, N-glycans are not the only parasite ligands for host galectins, as shown by the binding of T. vaginalis lipoglycan to human galectin-1 on epithelia (62).…”
Section: N-glycosylation Of Oyster Hemocytes and Plasma-usingmentioning
confidence: 99%
“…Sequence analysis indicated that PoGal2 consisted of two canonical galectin CRDs connected by linkers with 62 amino acid residues, which were longer than those of Manila clam (Kim et al, 2008) and snail (Yoshino et al, 2008). So far, the galectins with two CRDs were only isolated from Manila clam (Kim et al, 2008), abalone (ABN54798) and freshwater snail (Yoshino et al, 2008), which were typical tandem-repeat galectins (Leffler et al, 2004;Vasta et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A tandem-repeat galectin, McGal from Manila clam Ruditapes philippinarum, has also been proven to bind to the surface of Perkinsus olseni as PRR, and it is up-regulated after challenge with P. olseni or Vibrio tapetis (Kim et al, 2008). Another tandem-repeat galectin, BgGal from freshwater snail Biomphalaria glabrata, selectively recognizes the schistosome-related sugar lacNAc and strongly binds to hemocytes and the tegument of Schistosoma mansoni sporocysts in a sugar-inhibitable fashion (Yoshino et al, 2008). A multidomain galectin of eastern oyster Crassostrea virginica (CvGal) is responsible for recognizing the protozoan parasite Perkinsus marinus (Tasumi and Vasta, 2007).…”
Section: Introductionmentioning
confidence: 99%